Standardized hot water extract from the leaves of Hydrangea serrata (Thunb.) Ser. alleviates obesity via the AMPK pathway and modulation of the gut microbiota composition in high fat diet-induced obese mice. Issue 6 (3rd March 2021) - Han, Hee-Soo; Lee, Hwi-Ho; Gil, Hyo-Sun; Chung, Kyung-Sook; Kim, Jeon-Kyung; Kim, Dong-Hyun; Yoon, Jimin; Chung, Eun Kyoung; Lee, Jong Kil; Yang, Woong Mo; Shin, Yu-Kyong; Ahn, Hye Shin; et al.
Abstract : WHS prevented the HFD-induced obesity via regulating AMPK and AKT/mTOR signaling pathway. WHS might be a potential dietary supplement for alleviating obesity. Abstract : Obesity is an increasing health problem worldwide as it is the major risk factor for metabolic diseases. In the present study, we investigated the anti-obesity effects of WHS by examining its effects on high fat diet (HFD)-induced obese mice. Male C57BL/6 mice were fed either a normal diet (ND) or a high fat diet (HFD) with or without WHS. At the end of the experiment, we observed the changes in their body weight and white adipose tissue (WAT) weight and lipid profiles in plasma. We performed western blot and histological analyses of WAT and liver to elucidate the molecular mechanisms of action. We also conducted fecal 16S rRNA analysis for investigating the gut microbiota. Our results indicated that pre- and post-oral administration of WHS significantly prevented body weight gain and reduced body fat weight in HFD-induced obese mice. In addition, WHS was found to improve adipocyte hypertrophy and liver fat accumulation by regulating the AMPK and AKT/mTOR pathways. WHS ameliorated hyperlipidemia by reducing total cholesterol and low-density lipoprotein (LDL) and decreased the energy metabolism-related hormones, leptin and insulin, in mouse plasma. Furthermore, we found that WHS modulated gut dysbiosis by normalizing HFD-induced changes. Taken together, our in vivo data implicate that WHS can be considered as a potential dietary supplement for alleviating obesity.